Psychoanalysis as a Practice of Self-care (Andamios, Revista de Investigación Social, 2025)
In this piece of work, we address the complexity of relating the thoughts of Foucault and Freud, highlighting the difficulty of defining a synthesis between them and how they constantly intertwine and dissociate. We explore a possible reading of Freud from a Foucauldian perspective, focused on the relationships between practices of self, government, and truth. These connections lead us to think about the political dimension of psychoanalysis and reinforce the relationship between soul and government or psyche and power, shaping our analytical terrain. We find that psychoanalysis today can be configured as a practice of freedom that, as resistance, enables other possibilities of subjectivity away from optimization norms in techno-scientific governance.
Keywords: Psychoanalysis; epimeleia heautou; Freud; Foucault; politics